Art Practices and Urban Promenades: Belgrade's Knez Mihailova Street vs. Dionysius the Areopagite Promenade in Athens - Žakula (Serbia), Sonja; Đorđević Crnobrnja (Serbia), Jadranka (Bulletin of the Institute of Ethnography SASA; Vol 66 No 1 (2018): Historical Retrospectives of Ethnology and Anthropology, 2018)
Art Practices and Urban Promenades: Belgrade's Knez Mihailova Street vs. Dionysius the Areopagite Promenade in Athens